Professional certification, Applied Behavior Analysis and Autism Spectrum Disorder: contributions for a debate (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The provision of Applied Behavior Analysis (ABA) services for people with Neurodevelopmental Disorders has grown rapidly in Brazil, despite the profession not being officially established as a licensed occupation in the country, not even as a specialty of another profession. The purpose of this article is (a) to clarify aspects about the work of behavior analysts providing services in Brazil, (b) to point out the advantages of professional certifications to establish standards of performance and quality and (c) to carry out a comparative analysis of three certification programs in ABA. Fragilities in the Brazilian certification proposal are pointed out, especially concerning the requirements of supervised fieldwork and the absence of a code of ethics, and possible consequences of not correcting them.